Theatrical modernities in Brazil: circulation of modern ideas and practices through amateur groups and theatre critics in Natal from the 1940s to the 1960s - Moura, Monize Oliveira (Sala Preta, 2023)
In this study, we analyze the transformations in the amateur theatre in Natal, Brazil, from the 1940s to the 1960s, seeking to understand the extent to which it has spread and incorporated modern theatrical concepts. We consider that the consolidation of modern theatre in Brazil has related to a transnational process of affirming the idea of fine art theatre. By comparing three periodicals, we have observed: (a) the idea of theatrical renovation referred to the staging of plays acclaimed by their literary value and concerns with technical aspects of stage; and (b) the recurrence of the idea of regional theater to distinguish initiatives of scenic modernization. Such aspects suggest that Natal was connected, but not in a synchronic way, to the mentality that has dominated the field in other of the largest cities in Brazil.